(untitled) (Journal of School Administration Research and Development, 2020)
As the COVID-19 pandemic unfolded in K-12 education, school leaders quickly pivoted from prioritizing continuous instruction and technology access to the output, grades. In response to these unprecedented times, secondary schools utilized “do no harm” grading methods, such as freezing previous grades and replacing letter grades with pass-fail. The purpose of this essay is to describe grading principles that secondary school leaders should consider during future pandemic era learning, and to suggest implications based upon previous literature.